(untitled) (CAHIERS MAGELLANES-NS, 2024)
Hydropower is reliable renewable energy but there is occasionally debate on the negative social & environmental impacts caused by hydropower projects. The EIA is an instrument which is the most important tool in achieving sustainability for such hydropower projects. An EIA takes into consideration direct or indirect effects on land, water, air, flora, fauna and the living community near the propped projects. However there are several hurdles also which obstruct the implementation of EIA regulations in most of the countries throughout the globe. Studies have been carried out by many researchers to understand the requirement of EIA for hydropower projects. This paper presents a literature review of EIA with special reference to Hydroelectric Projects in respect of some countries viz India, Pakistan, Canada, Brazil, Turkey, Colombia, Ecuador, Laos, Mexico and Kenya. The work explores researchers' perspectives in the aforementioned countries so as to improve the quality and effectiveness of EIA procedures.